Lon recognition of the replication initiator DnaA requires a bipartite degron. Issue 1 (8th November 2018) - Liu, Jing; Zeinert, Rilee; Francis, Laura; Chien, Peter
Summary: DnaA initiates chromosome replication in bacteria. In Caulobacter crescentus, the Lon protease degrades DnaA to coordinate replication with nutrient availability and to halt the cell cycle during acute stress. Here, we characterize the mechanism of DnaA recognition by Lon. We find that the folded state of DnaA appears crucial for its degradation, in contrast to the well‐known role of Lon in degrading misfolded proteins. We fail to identify a single degradation motif (degron) sufficient for DnaA degradation, rather we show that both the ATPase domain and a species‐specific N‐terminal motif are important for productive Lon degradation of full‐length DnaA. Mutations in either of these determinants disrupt DnaA degradation in vitro and in vivo . However, analysis of truncation products reveals that appending other extensions to the ATPase domain is sufficient to trigger degradation, suggesting plasticity in Lon recognition. Our final working model is that Lon engages DnaA through at least two elements, one of which anchors DnaA to Lon and the other acting as an initiation site for degradation. Abstract : In Caulobacter, the Lon protease degrades the replication initiator DnaA. Here, we show that rather than relying on a single degron, Lon recognizes multiple sequence determinants in DnaA for robust proteolysis. This type of multipartite recognition is seen in other energy‐dependent protease systems and likely reflects a general principle in protease recognition.